Marketing Mix Analysis that Influence Buy Interest Vegetables Types of Lettage Lactuca Sativa (Case Study of UMKM Marasa Farm Pinrang District) - Irmayani; Ferry Awal; Yusriadi; Irninthya Nanda Pratami Irwan (East Asian Journal of Multidisciplinary Research, 2022)
Research has also been conducted to examine whether the 7P marketing mix has an influence in generating interest in buying Lactuca Sativa lettuce at Mara Farm. The method of determining the location is done by using the method (Purposive Sampling). While the determination of the sample in this study uses (incidental sampling), namely the determination of the sample that accidentally meets the researcher. The methods of collecting data in this study are interviews, questionnaires, observations and documentation. Instrument testing is done by testing the validation and reliability using the SPSS program. The data analysis method used is qualitative data analysis to identify the marketing mix that has been carried out by Marasa Farm and also quantitative data analysis to determine the effect of the marketing mix on purchasing decisions at Marasa Farm. So the results of this study indicate that the marketing mix which consists of Product, Process and Physical Evidence variables partially has a significant influence on buying interest with a significance value below 0.05% while the Price, Place, Promotion and Human Resources variables partially have no significant effect. significant.